Targeted HIV seroprevalence among Vietnamese in southern California. Issue 4 (August 1994) - Gellert, G A; Moore, D F; Maxwell, R M; Mai, K K; Higgins, K V
Abstract : OBJECTIVE–The prevalence of HIV among southern California Vietnamese is unknown. We collected seroprevalence data on targeted Vietnamese in Orange County, California who may be at risk for HIV infection. METHODS–The assumption of elevated risk was based on rates of infection reported among other U.S. groups. Vietnamese (N = 874) from six county sites were tested during 1992: (1) attendees at county HIV/STD clinics and (2) IDU program; (3) male inmates of the county jail and (4) of a juvenile detention centre; (5) males in a driving under the influence of alcohol (DUI) remedial program; and (6) patients for nonpregnancy-related syphilis screening. RESULTS–The number of cases detected and risk factors were: (1) county HIV/STD clinics–5/223 (2.3%), all men who had sex with men; (2) men's jail–1/122 (0.8%), risk factors unknown; (3) juvenile hall–1/145 (0.7%), risk factors unknown; (4) IDU program–0/33; (5) syphilis screening–0/284; and (6) DUI program–0/67. CONCLUSIONS–HIV infection exists among southern California Vietnamese, and men who have sex with men appear to be at a risk for HIV infection similar to others practicing high risk behaviors in the U.S. population. Preventive education needs to be targeted explicitly at these individuals.